Aberrations in Sperm Morphology and Sperm Production Parameters in Rats Exposed to Methyl Mercuric Chloride - Karunasri, V.; Nagamalleswari, Y.; Kishore, P. V.S.; Raghunath, M. (Indian Journal of Veterinary Anatomy, 2018)
The study was conducted on 36 adult male Sprague Dawley rats of 6 weeks age. These subjects were randomly assignedinto three groups, viz. control (group I), 2.5ppm methyl mercury (group II) and 5.0ppm methyl mercury exposure (group III).Methyl mercury was fed in drinking water daily for a period of 35 days. A normal spermatozoon of rat consists of hook shapedhead with straight tail. In the present study various morphological abnormalities were observed in the semen smears of treatedgroups(absence of head, absence of tail, banana shaped head, cone shaped head, coiling of tail, coiling of head, double head,kink in the mid piece and clogging of spermatozoa). There was a significant increase in the mean sperm count in rats of 2.5ppmgroup than in other groups at 14 and 35 days post exposure. In 35 days of post exposure both 2.5 and 5.0ppm showed a significant difference with respect to the number of head and tail abnormalities than control group in post hoc test. There was a sudden heave in the average serum total testosterone at 14 days post exposure in 2.5ppm and 5.0ppm (3.36±0.495 and 8.41±3.125ng/ml respectively) than control group (1.386±0.232 mg/ml) which may be resulted with increased mean sperm count, in-turn resulting in male infertility due to the production of abnormal sperms at an early age.